2011
DOI: 10.1024/1661-8157/a000491
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolyse unter der Kombination Atorvastatin, Amiodaron und Fluconazol

Abstract: A 67-year old man was hospitalized due to an aorto-coronary bypass and cecal perforation. After administration of atorvastatin, amiodarone, and fluconazole, rhabdomyolysis developed with electrolyte disturbances (hyperphosphatemia, hyopcalcemia) and a massive increase in creatine kinase and myoglobin. In the clinical course, other complications manifested such as acute renal failure, critical illness myopathy, acute gout on the knee, and sternal infection with coagulase-negative staphylococci. After stopping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Wang et al in 2017 reported a case of sudden cardiac arrest in a patient treated simultaneously with uconazole and amiodarone [29]. Another reported life-threatening side effect of multiple therapies in a patient taking atorvastatin, amiodarone, and uconazole was rhabdomyolysis [30]. These reports question the safety of treatment with azole in patients with polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al in 2017 reported a case of sudden cardiac arrest in a patient treated simultaneously with uconazole and amiodarone [29]. Another reported life-threatening side effect of multiple therapies in a patient taking atorvastatin, amiodarone, and uconazole was rhabdomyolysis [30]. These reports question the safety of treatment with azole in patients with polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although triazole antifungal agents are poorly metabolized by one-step oxidative biotransformation and are excreted through the kidneys in the urine in the form of prototype drugs (Lass-Florl, 2011), they showed definite inhibitory effects on CYPs and significantly increased systemic exposure to drugs metabolized by CYP3A4, such as fentanyl and diazepam (Saari et al, 2007;Saari et al, 2008). In addition, as a moderate CYP3A inhibitor, fluconazole may lead to rhabdomyolysis in some clinical cases with concomitant use of ATO or simvastatin (Kahri et al, 2005;Franz et al, 2011). VOR is a derivative of fluconazole and has been identified as an inhibitor of CYP3A (Kim et al, 2019), which may be a critical factor in the elevated serum levels of tacrolimus (Imamura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between ketokonazole and simvastatin (49-51) or lovastatin (52) have also been described. Rhabdomyolysis as a consequence of fluconazole interaction with statins has been reported as well (53)(54)(55)(56).…”
Section: Major Statin-drug Interactionsmentioning
confidence: 99%